2020
DOI: 10.3390/agronomy10030411
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Different Types of Trichomes in Tomato Resistance to Cold, Drought, Whiteflies, and Botrytis

Abstract: The tomato (Solanum lycopersicum) is one of the most popular vegetables in the world. In tomato production, due to the effects of diseases, insect pests, drought, and cold damage, large-scale production reduction is often caused. Plant trichomes are protruding attachments distributed on the surface of different plants, providing protection for plants. When the plant is under external stress, the trichomes can play an important role in protecting the plant from damage through its physical structure. The density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 29 publications
(45 reference statements)
1
32
0
Order By: Relevance
“…Hase et al [17,63] showed that the frequency of DNA mutations, including single-substitutions, small InDels, and DNA structural variation, increased when irradiation was applied at higher doses. Trichomes are specialized cells that undergo differentiation from the epidermis of plants and play an essential role in conferring protection to plants against various biotic and abiotic stresses [64][65][66]. We detected a decrease in the density of type VI trichomes on leaves when gamma rays were used for chronic irradiation at a dose of 100-200 Gy for 4 weeks.…”
Section: Discussionmentioning
confidence: 82%
“…Hase et al [17,63] showed that the frequency of DNA mutations, including single-substitutions, small InDels, and DNA structural variation, increased when irradiation was applied at higher doses. Trichomes are specialized cells that undergo differentiation from the epidermis of plants and play an essential role in conferring protection to plants against various biotic and abiotic stresses [64][65][66]. We detected a decrease in the density of type VI trichomes on leaves when gamma rays were used for chronic irradiation at a dose of 100-200 Gy for 4 weeks.…”
Section: Discussionmentioning
confidence: 82%
“…S2A) [ 38 , 43 ]. According to our assessment, these trichomes represent the glandular type I and type VI trichomes as well as non-glandular trichomes of the types II and III [ 44 ]. In case of N. benthamiana , microscopy revealed two types of glandular trichomes (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Solyc07g054840.3.1 (Log 2 Fc = 3.34; tomato transcription factor 41) shares the best homology with Myb41 of A. thaliana where it functions as a Map-kinase involved in several signaling pathways that control plant development and salt stress tolerance ( Hoang et al, 2012 ). Solyc03g095810.3.1 (Log 2 Fc = 6.92; tomato Trichome birefringence-like protein) upregulation mediates xylan acetylation and has been demonstrated essential in tomatoes for invading microorganism resistance and against environmental stress like cold and drought ( Zhang et al, 2020 ). Solyc10g007970.2.1 (Log 2 Fc = 6.96; tomato WRKY transcription factor 77) has been demonstrated to be involved in the signaling to water deficit in tomatoes ( Asins et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%